Pengaruh Harga Dan Produktivitas Kelapa Sawit Terhadap Kesejahteraan Petani Di Desa Janji Kecamatan Bilah Barat Kabupaten Labuhanbatu - Erlinda Sari Ritonga; Yudi Triyanto; Kamsia Dorliana Sitanggang (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
This study discusses the effect of oil palm prices and productivity on the welfare of oil palm farmers in Promise Village, Bilah Barat District, Labuhanbatu Regency. The problem under study is how much influence price and productivity have on the welfare of farmers. The background of this research is that the price of palm oil has decreased every month. This study aims to determine the effect of oil palm price and productivity on the welfare of farmers in Promise Village, West Bilah Subdistrict, Labuhanbatu Regency. The benefit of this research is that farmers take better care of their oil palm land and so that price productivity is in line with their expectations. This research method uses a questionnaire taken directly from the source. The data of this study are primary data. The data analysis technique used is multiple linear regression analysis assisted by SPSS (Statistical Package for Social Science) software 22. The results of this study indicate that (1) the price of oil palm has a positive and significant effect on the welfare of oil palm farmers in Promise Village, Bilah District. West Labuhanbatu Regency. (2) Oil palm productivity also has a very positive effect on the welfare of oil palm farmers in Promise Village, Bilah Barat District, Labuhanbatu Regency. Keywords: Price, Productivity and Welfare